The Love Nest - Keaton, Buster, 1895-1966; Buster Keaton Productions; Cinetel Films ([United States] : Buster Keaton Productions, 1923)
In an attempt to forget his lost sweetheart, Buster takes a long trip at sea where he boards a whaling ship with a strict captain. --
"A First National attraction."
Buster Keaton, Joe Roberts, Virginia Fox.
Cinematographer, Elgin Lessley.
Silent, with English intertitles and musical accompaniment.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Ships -- Drama; Whaling masters -- Drama; Whalers (Persons) -- Drama; Whaling ships -- Drama; Short films; Comedy films; Silent films; Feature films; Internet videos; Streaming video